2016
DOI: 10.1111/jam.13066
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of Campylobacter contamination on broiler farms; external and internal sources

Abstract: This study has established the pattern of Campylobacter contamination on broiler farms, identified an early detection opportunity, highlighted the need to better understand the role of viable but nonculturable Campylobacter in the ecology of Campylobacter on broiler farms and demonstrated the need for improved biosecurity to prevent the spread of Campylobacter from within the house to the surrounding environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Periods of over 14 days can decrease the possibility of residual bacterial contamination (Newell et al, 2011). The benefit of longer turnaround periods is also supported by Battersby et al (2016) who state that rapid flock turnover contributes to Campylobacter carry over with increased risk being reported if houses are restocked within 9 days of depopulation. A study by Jonsson et al (2012) also investigated the effect of the length of time the house was empty.…”
Section: Cleaning and Disinfectionmentioning
confidence: 90%
See 4 more Smart Citations
“…Periods of over 14 days can decrease the possibility of residual bacterial contamination (Newell et al, 2011). The benefit of longer turnaround periods is also supported by Battersby et al (2016) who state that rapid flock turnover contributes to Campylobacter carry over with increased risk being reported if houses are restocked within 9 days of depopulation. A study by Jonsson et al (2012) also investigated the effect of the length of time the house was empty.…”
Section: Cleaning and Disinfectionmentioning
confidence: 90%
“…Biosecurity is an important measure for the control of Campylobacter because once colonization occurs in a poultry flock the horizontal transmission can be rapid (Battersby et al, 2016). A study by Gibbens et al (2001) demonstrated that well-implemented disinfection protocols could lead to a decrease in Campylobacter prevalence from 80 to less than 40% in broilers (Gibbens et al, 2001).…”
Section: Biosecuritymentioning
confidence: 99%
See 3 more Smart Citations